Epidemiological trends of cryptococcosis in Italy: Molecular typing and susceptibility pattern of Cryptococcus neoformans isolates collected during a 20-year period. (23rd January 2018) - Cogliati, Massimo; Prigitano, Anna; Esposto, Maria Carmela; Romanò, Luisa; Grancini, Anna; Zani, Alberto; Tortorano, Anna Maria
Abstract: In the present study clinical data and isolates from cases of cryptococcosis recorded during clinical surveys carried out in Italy from 1997 to 2016, were investigated. Molecular typing and antifungal susceptibility testing were performed in order to delineate the epidemiological trend of cryptococcosis in Italy and to define wild-type population for four different antifungal compounds. During the studied period, a total of 302 cases collected from 32 centers of 11 Italian regions were recorded. Analysis of clinical data showed a significant increase of frequency (from 7% to 38%) of cryptococcosis in human immunodeficiency virus (HIV)-negative patients primarily with hematologic malignancies and solid organ transplantations. The prevalence of the molecular types has significantly changed during the study period, showing an increase of VNIII isolates from 11% to 41% in HIV-negative patients, and a decrease of VNIV isolates from 36% to 16%. Antifungal susceptibility testing allowed us to calculate the epidemiological cut-off for flucytosine (1 mg/l), fluconazole (8 mg/l), itraconazole (0.5 mg/l), and voriconazole (0.25 mg/l). Most of the isolates were wild-type strains. Comparison of the MIC distributions according to molecular types showed that VNIV isolates had lower MICs for fluconazole and itraconazole than the VNI and VIII isolates. The current study emphasizes that the epidemiology of cryptococcosis in Italy has significantly changed over the last decades.